2003
DOI: 10.2190/ftg3-q9t0-7u26-5q5x
|View full text |Cite
|
Sign up to set email alerts
|

The Illusion of Independent Agency: Do Adult Fiction Writers Experience Their Characters as Having Minds of Their Own?

Abstract: The illusion of independent agency (IIA) occurs when a fictional character is experienced by the person who created it as having independent thoughts, words, and/or actions. Children often report this sort of independence in their descriptions of imaginary companions. This study investigated the extent that adult writers experience IIA with the characters they create for their works of fiction. Fifty fiction writers were interviewed about the development of their characters and their memories for childhood ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 13 publications
5
38
0
1
Order By: Relevance
“…Those who had imaginary companions as children also scored higher on their interpersonal style toward others, and on internal state awareness, which is consistent with the finding that children with imaginary companions tend to be socially oriented and accommodating (e.g., Manosevitz, Fling, & Prentice, 1977;Singer & Singer, 1990;Seiffge-Krenke, 1997). Taylor, et al (2003) reported that creative writers, a large percentage of whom had imaginary companions as children, scored higher than the general population on the four subscales of the Interpersonal Reactivity Index (Davis, 1983), which measures predisposition to fantasy, perspective taking, empathic concern, and personal distress. Such findings are consistent with the social orientation associated with a keen imaginative life.…”
Section: Resultssupporting
confidence: 79%
“…Those who had imaginary companions as children also scored higher on their interpersonal style toward others, and on internal state awareness, which is consistent with the finding that children with imaginary companions tend to be socially oriented and accommodating (e.g., Manosevitz, Fling, & Prentice, 1977;Singer & Singer, 1990;Seiffge-Krenke, 1997). Taylor, et al (2003) reported that creative writers, a large percentage of whom had imaginary companions as children, scored higher than the general population on the four subscales of the Interpersonal Reactivity Index (Davis, 1983), which measures predisposition to fantasy, perspective taking, empathic concern, and personal distress. Such findings are consistent with the social orientation associated with a keen imaginative life.…”
Section: Resultssupporting
confidence: 79%
“…In fact, when the diversity of plural experience is considered, multiplicity may seem to be less of an extraordinary achievement and more of a fundamentally human experience. Many fiction writers, for example, report that the characters of their design seem to come to life in their heads, behaving autonomously and being perceived as full-fledged consciousnesses [19]. Religious individuals of faiths where the God, Gods, or spirits they believe in can interact with them to a degree report similar phenomena, regardless of their specific religion or culture [20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pearson et al (2001) found that 28% of children age 5 to 12 years had imaginary companions. In addition, there is evidence that many adolescents write to imaginary companions in their diaries (Seiffge-Krenke, 1997) and that imaginary companions might have developmental ties with creative activities in adulthood (Taylor, Hodges, & Kohanyi, 2003). …”
mentioning
confidence: 99%